Geothermal Energy: Revolutionary Initiative in Indian Dairy Sector and Its Effect on Physiological Parameters of Growing Murrah Buffaloes - Bhalakiya, Nikita; Singh, Sohan Vir; Singh, Pawan; Kumar, Gaurav; Kaur, Jaskiran; Ukey, Apeksha (Indian Journal of Veterinary Sciences and Biotechnology, 2025)
Renewable energy derived from the core of earth is known as geothermal energy. It originates from heat produced during the radioactive decay of elements. The temperature at 2-3 meters below the surface of earth remains almost the same in a special range (24°-28°C) throughout the year. This temperature can be used to control the temperature of the animal habitat in a comfortable range during the summer and winter seasons by applying geothermal system. Geothermal system was developed through results obtained of a pilot study conducted in LRC, NDRI, Karnal in which various temperature sensors were used to detect temperature at various underground depth, i.e., 12, 8, 6, 4, and 2 meter. The effect of surface (environmental) temperature was found negligible on underground temperature beyond 4 m depth. Therefore, geothermal heat exchanger/pipes can be placed at 4 m depth below. The efficiency of this geothermal system was determined for cooling and warming of shed and its impact on physiological parameters of 18 growing female Murrah buffalo-heifers (10-14 month) divided into 3 equal groups during winter and summer seasons at ICAR-NDRI, Karnal. Animals of first group (experimental) were housed under shed provided with geothermal system, those of second group (control-I) were housed in the shed which was replica of group I, except geothermal system, and third group of animals (control-II, herd) were reared under normal existing managemental conditions. The system was operated during coldest 12 hours of the day (night time) during winter season and hottest 12 hours of the day (day time) during summer season. Temperature difference among experimental shed, control-I, control-II and duct were recorded throughout the study at every 2 h interval by temperature sensing probe. Samplings were done at fortnight intervals. During the experimental period we found significant (p<0.05) increase in temperature of experimental shed during winter season, and significant decrease (p<0.05) during summer season as compared to environmental temperature and control shed. This effect was reflected in terms of significantly (p<0.05) higher physiological parameters, viz., respiration rate, rectal temperature and skin temperature during winter season and lower during summer season in experimental shed as compared to herd and control group.